The Influence of Job Rotation and Job Operational Standards on Employee Achievement - Roza Noverita; Afni Yeni; Wahyu Indah Mursalini (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research aims to determine the effect of work rotation and work operational standards on the work performance of BKPSDM employees in Solok Regency with a sample of 38 respondents who were studied using quantitative methods. Based on the results of statistical analysis, it can be interpreted that Job Rotation partially has a significant effect on Employee Work Performance, this is proven by the t test with a significant value of tcount 5.360 > ttable 2.030 in the significance level value, 0.000 < 0.0. So it can be interpreted that job rotation has a significant effect on employee work performance. Based on the results of statistical analysis, it can be concluded that Work Operational Standards partially have a significant effect on the Work Performance of Solok Regency BKPSDM Employees. This is proven by the T test with a significant value of tcount 2.691 > t table 2.030 and a significance level value of 0.011 < 0.05. So it can be concluded that Work Operational Standards have a significant effect on the Work Performance of Solok Regency BKPSDM Employees. Simultaneously, Job Rotation and Work Operational Standards have a significant effect on the Job Performance of Solok Regency BKPSDM Employees. This is proven by using the F test with a significant value of fcount 21.159 > ftable 3.27 and the resulting significant value is 0.000 and this value is much smaller than a (0.05). This can also be seen from the R Square value obtained at 0.547 or 54.7% and the remaining 45.3% is influenced by other variables not included in this research. Keywords: Job Rotation, Work Operational Standards, and Work Performance